Fisetin Inhibits Osteoclastogenesis Through Prevention of RANKL-Induced ROS Production by Nrf2-Mediated Up-regulation of Phase II Antioxidant Enzymes - Eiko Sakai; Megumi Shimada-Sugawara; Yu Yamaguchi; Hiroshi Sakamoto; Reiko Fumimoto; Yutaka Fukuma; Kazuhisa Nishishita; Kuniaki Okamoto; Takayuki Tsukuba (Elsevier, 2013)
Abstract.: Osteoclasts (OCLs) are multinucleated bone-resorbing cells that are differentiated by stimulation with receptor activator of nuclear factor kappa-B ligand (RANKL) and macrophage colony-stimulating factor. We recently demonstrated that regulation of heme-oxygenase 1 (HO-1), a stress-induced cytoprotective enzyme, also functions in OCL differentiation. In this study, we investigated effects of fisetin, a natural bioactive flavonoid that has been reported to induce HO-1 expression, on the differentiation of macrophages into OCLs. Fisetin inhibited the formation of OCLs in a dose-dependent manner and suppressed the bone-resorbing activity of OCLs. Moreover, fisetin-treated OCLs showed markedly decreased phosphorylation of extracellular signal-regulated kinase, Akt, and Jun N-terminal kinase, but fisetin did not inhibit p38 phosphorylation. Fisetin up-regulated mRNA expression of phase II antioxidant enzymes including HO-1 and interfered with RANKL-mediated reactive oxygen species (ROS) production. Studies with RNA interference showed that suppression of NF-E2-related factor 2 (Nrf2), a key transcription factor for phase II antioxidant enzymes, rescued fisetin-mediated inhibition of OCL differentiation. Furthermore, fisetin significantly decreased RANKL-induced nuclear translocation of cFos and nuclear factor of activated T cells cytoplasmic-1 (NFATc1), which is a transcription factor critical for osteoclastogenic gene regulation. Therefore, fisetin inhibits OCL differentiation through blocking RANKL-mediated ROS production by Nrf2-mediated up-regulation of phase II antioxidant enzymes. Keywords:: osteoclast, fisetin, reactive oxygen species (ROS), NF-E2-related factor 2 (Nrf2), nuclear factor of activated T cells cytoplasmic-1 (NFATc1)